A bacterium‐like particle vaccine displaying Zika virus prM‐E induces systemic immune responses in mice. Issue 5 (2nd June 2022) - Jin, Hongli; Bai, Yujie; Wang, Jianzhong; Jiao, Cuicui; Liu, Di; Zhang, Mengyao; Li, Entao; Huang, Pei; Gong, Zhiyuan; Song, Yumeng; Xu, Shengnan; Feng, Na; et al.
Abstract: The emergence of Zika virus (ZIKV) infection, which is unexpectedly associated with congenital defects, has prompted the development of safe and effective vaccines. The Gram‐positive enhancer matrix‐protein anchor (GEM‐PA) display system has emerged as a versatile and highly effective platform for delivering target proteins in vaccines. In this study, we developed a bacterium‐like particle vaccine, ZI‐△‐PA‐GEM, based on the GEM‐PA system. The fusion protein ZI‐△‐PA, which contains the prM‐E‐△TM protein of ZIKV (with a stem‐transmembrane region deletion) and the protein anchor PA3, was expressed. The fusion protein was successfully displayed on the GEM surface to form ZI‐△‐PA‐GEM. Moreover, the intramuscular immunization of BALB/c mice with ZI‐△‐PA‐GEM combined with ISA 201 VG and poly(I:C) adjuvants induced durable ZIKV‐specific IgG and protective neutralizing antibody responses. Potent B‐cell/DC activation was also stimulated early after immunization. Notable, splenocyte proliferation, the secretion of multiple cytokines, T/B‐cell activation and central memory T‐cell responses were elicited. These data indicate that ZI‐△‐PA‐GEM is a promising bacterium‐like particle vaccine candidate for ZIKV.